2021
DOI: 10.1063/5.0067525
|View full text |Cite
|
Sign up to set email alerts
|

Anharmonicity of optical phonon modes in copper doped rutile TiO2 nanorod composed microflowers

Abstract: Anharmonicity and impurities have a significant impact on the dynamic and optical properties of crystalline solids. In this report, we have performed temperature-dependent Raman spectroscopy in the range of 300–800 K for hydrothermally synthesized titanium dioxide (TiO2) nanorod composed microflowers doped with Cu. X-ray diffraction and high resolution transmission electron microscopy confirm the pure rutile phase of both pristine and Cu doped TiO2. The most intense Eg and A1g modes exhibit a frequency redshif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Firstly, the Au decoration on the surface of TiO 2 suppresses the out-of-plane vibration of O atoms, and stress develops, which causes the shift of the Raman peak position. Secondly, it is reported that the E g vibrational mode gets red-shifted with increasing temperature [43,49]. It is also demonstrated that localized heat is generated in Au upon photoexcitation near its SPR.…”
Section: Spectroscopic Characterizationmentioning
confidence: 92%
See 2 more Smart Citations
“…Firstly, the Au decoration on the surface of TiO 2 suppresses the out-of-plane vibration of O atoms, and stress develops, which causes the shift of the Raman peak position. Secondly, it is reported that the E g vibrational mode gets red-shifted with increasing temperature [43,49]. It is also demonstrated that localized heat is generated in Au upon photoexcitation near its SPR.…”
Section: Spectroscopic Characterizationmentioning
confidence: 92%
“…The TiO 2 seed layer was prepared on Si using the radio-frequency sputtering deposition technique with working pressure 5 × 10 −3 mbar and in an Ar flow rate of 15 sccm. Subsequently, TiO 2 microflowers were grown on the seeded substrate using the hydrothermal method as described in our earlier publication [43]. An appropriate quantity of HCl was added with deionized water, stirred well for 15 min, and an appropriate amount of titanium butoxide was added to the above solution dropwise and stirred until a clear solution was obtained.…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, from the ICP-OES measurement, the actual doping % was found to be approximately 50% of the initial value taken at the time of the experiment as reported in our previous work. 34…”
Section: Methodsmentioning
confidence: 99%
“…The TD peak shift of a Raman phonon mode provides valuable information on the effect of thermal perturbation on phonon scattering processes and causes Raman peak broadening due to reduced lifetime with thermal expansion of the crystal lattice. Raman study on anatase TiO 2 nanorods (TNRs) has been carried out to a great extent, 50–52 whereas that od rutile phase has been carried out only by a few research groups, 40,53,54 and carrying out more studies is required to present a holistic picture about the different aspects related to anharmonicity in low dimensional TiO 2 .…”
Section: Introductionmentioning
confidence: 99%